MODERN REALITIES OF DIGITALIZATION OF SOCIETY IN THE FIELD OF SOCIAL AND LABOR RELATIONS - DEREVYANKO, Denis; PYROH, Yevhenii; BARDADYM, Oleh; SHPYLIOVYI, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the transformation of social and labor relations in the context of society’s digitalization, which has become one of the defining trends of modern global development. Under the influence of digital technologies, profound changes occur in the organization of work, human resource management, and social interaction. The author substantiates that traditional forms of employment, based on long-term labor relations and fixed workplaces, are increasingly being replaced by flexible, remote, and platform-based models of work. This evolution in the labor sphere enhances workforce mobility, optimizes labor processes, and expands opportunities for professional self-realization, while simultaneously creating new challenges related to social protection, the safeguarding of labor rights, and maintaining a balance between flexibility and employment stability. The article emphasizes that the digital economy stimulates the formation of new labor relations in which digital competencies, adaptability, and continuous professional development play a crucial role.The study synthesizes the findings of leading Ukrainian scholars, including N. Azmuk, D. Bohynia, O. Hrishnova, A. Kolot, and E. Libanova, who have identified key patterns in the evolution of social and labor relations in the digital era. It is highlighted that modern institutional mechanisms of labor regulation do not fully account for the challenges of digitalization, while traditional tools for ensuring social security are not always compatible with gig, remote, or project-based employment. These trends underscore the need to modernize labor legislation, establish effective systems of social insurance for workers in new forms of employment, and develop infrastructures for reskilling and lifelong learning.The research identifies the main directions of labor transformation. Firstly, automation and artificial intelligence are reshaping the labor market structure by reducing demand for routine occupations and increasing the value of creative and analytical skills. Secondly, digital platforms create new employment channels that require specific mechanisms of taxation, social protection, and collective representation. Thirdly, remote and hybrid work necessitate new standards for organizing working time, communication, and occupational safety. The author argues that effective adaptation of social and labor systems to the conditions of the digital economy requires cross-sector cooperation among the state, business, and trade unions, aimed at establishing an inclusive and socially responsible labor model.The conclusions emphasize that digitalization is not only a technological process but also a strategic direction in the evolution of social and labor relations. It creates new opportunities for productivity growth, flexibility, and workforce competitiveness, while simultaneously exacerbating issues of digital inequality, job displacement due to automation, and the need to redefine social guarantees. The paper proposes key guidelines for modernizing labor resource management systems, including the development of new mechanisms for protecting the rights of digital economy workers, integrating digital tools into social dialogue, and designing adaptive employment strategies. Thus, digital transformation is conceptualized as a complex process that requires the rethinking of economic, social, and legal approaches to work organization, fostering the development of innovative employment models and strengthening the resilience of the labor market in the future.
Keywords: digitalization of society; social and labor relations; employment transformation; flexible forms of work; remote work; gig economy; social security